Elementary and middle school mathematics : Teaching developmentally - Van de Walle, John A. (Boston : New York : San Francisco : Pearson, 2004)
Presents a resource for teaching mathematics, providing perspectives on how to help children learn math, and addressing every major topic of the kindergarten through eighth grade mathematics curriculum.
Includes bibliographical references and index.
Keywords: Mathematics. -- Study and teaching (Elementary); Mathematics -- Study and teaching (Middle school)